1988
DOI: 10.1182/blood.v71.2.383.bloodjournal712383
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors influencing the efficacy of pooled platelet transfusions

Abstract: To determine the relative importance of clinical factors on the efficacy of platelet transfusions, 941 pooled platelet transfusions from HLA-unmatched donors were studied prospectively in 133 patients with bone marrow failure. Multiple linear regression analyses identified the major factors influencing one-hour-corrected increments (CI) as prior splenectomy, bone marrow transplantation, disseminated intravascular coagulation, concurrent intravenous amphotericin B, splenomegaly, and HLA antibody grade. The rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
2

Year Published

1995
1995
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 0 publications
3
77
2
Order By: Relevance
“…Time from transfusion to posttransfusion platelet count 02. PRA level (0, 1-10%, 10-80%, or 80-100%) 03. Fever (temperature >38.5°C during the 6 hours before or after transfusion) 04.…”
Section: Evaluating the Effectiveness Of Platelet Transfusionsmentioning
confidence: 99%
“…Time from transfusion to posttransfusion platelet count 02. PRA level (0, 1-10%, 10-80%, or 80-100%) 03. Fever (temperature >38.5°C during the 6 hours before or after transfusion) 04.…”
Section: Evaluating the Effectiveness Of Platelet Transfusionsmentioning
confidence: 99%
“…With the increased use of high-dose chemotherapy and the absence of a clinically reliable megakaryocytic growth factor, platelet transfusion continues to be the standard support for amegakaryocytic thrombocytopenia (Bishop et al, 1988). Patients receiving myeloablative therapy will possibly require amphotericin-B prophylaxis and/or therapy, as well as platelet transfusion support (Terrell & Hughes, 1992;Riley et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Often both supportive care modalities are used together (Heyman et al, 1990). Bishop et al (1988) have demonstrated, in a retrospective study, that the presence of amphotericin-B in the medical regimen of transfused patients negatively influences platelet recovery. Their study does not address the timing of administering both therapies, however.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations